Opportunity for genome engineering to enhance phosphate homeostasis in crops - Abdullah, Siti Nor Akmar; Ariffin, Norazrin; Md Hatta, Muhammad Asyraf; Kemat, Nurashikin (Springer, 2024)
Plants maintain cellular homeostasis of phosphate (Pi) through an integrated response pathway regulated by diferent families of transcription factors including MYB, WRKY, BHLH, and ZFP. The systemic response to Pi limitation showed the critical role played by inositol pyrophosphate (PP-InsPs) as signaling molecule and SPX (SYG1/PHO81/XPR1) domain proteins as sensor of cellular Pi status. Binding of SPX to PP-InsPs regulates the transcriptional activity of the MYB-CC proteins, phosphate starvation response factors (PHR/PHL) as the central regulator of Pi-defciency response in plants. Vacuolar phosphate transporter, VPT may sense the cellular Pi status by its SPX domain, and vacuolar sequestration is activated under Pi replete condition and the stored Pi is an important resource to be mobilized under Pi defciency. Proteomic approaches led to new discoveries of proteins associated with Pi-defcient response pathways and post-translational events that may infuence plants in achieving Pi homeostasis. This review provides current understanding on the molecular mechanisms at the transcriptional and translational levels for achieving Pi homeostasis in plants. The potential strategies for employing the CRISPR technology to modify the gene sequences of key regulatory and response proteins for attaining plant Pi homeostasis are discussed.